2004
DOI: 10.1038/sj.embor.7400123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reciprocal chromosomal translocations on the fitness of Saccharomyces cerevisiae

Abstract: Yeast species have undergone extensive genome reorganization in their evolutionary history, including variations in chromosome number and large chromosomal rearrangements, such as translocations. To determine directly the contribution of chromosomal translocations to the whole organism's fitness, we devised a strategy to construct in Saccharomyces cerevisiae collinear 'evolutionary mimics' of other species originally differing by the presence of reciprocal translocations in their genome. A modification of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 24 publications
2
34
1
1
Order By: Relevance
“…The results of Colson et al 29 support a model where natural selection is responsible for the fixation of CRs between yeast species. However, the CRs tested in this study were naturally occurring and so we may expect them to be either neutral or advantageous, as strongly deleterious CRs are unlikely to be fixed in natural populations.…”
supporting
confidence: 72%
“…The results of Colson et al 29 support a model where natural selection is responsible for the fixation of CRs between yeast species. However, the CRs tested in this study were naturally occurring and so we may expect them to be either neutral or advantageous, as strongly deleterious CRs are unlikely to be fixed in natural populations.…”
supporting
confidence: 72%
“…(42) Additionally, when experimental approaches are used to monitor speciation, genome-level changes are commonly observed features. (43,44) Interestingly, the same phenotype of drug resistance in fungi can be generated by different gene-defined ''pathways,'' thus reducing the importance of any single gene in the process. (45) A recent finding in cancer cells demonstrates that the development of drug resistance results from the generation of cells with different karyotypes, which display totally different molecular pathways (Heng, unpublished data).…”
Section: Selection Of Genetic Network Rather Than Genes or Pathways:mentioning
confidence: 99%
“…The host with translocated genes might be able to adapt to a new niche faster than if it depended solely on substitution. Indeed, it has been shown that large-scale genome rearrangements, such as gene inversion and gene translocation, alter gene expression (Brinig et al 2006) and might play roles in niche adaptation (Colson et al 2004;Kuwahara et al 2004;Burgetz et al 2006;Coleman et al 2006;Liu et al 2006).…”
Section: Discussionmentioning
confidence: 99%